47‐4: Effects of Fine‐Metal‐Mask Wrinkling on OLED Patterning Defects. Issue 1 (30th May 2018) - Zhu, Haibin; Wang, Weijie; Zhang, Fengjie; Jin, Xin; Li, Xiaohu; Wang, Xinxing; Zhang, Bin; Yuan, Guangcai
Abstract : Fine‐metal‐mask (FMM) technology has been the remaining bottleneck for the wide application of OLEDs, since it is crucial to evaporation patterning defects. The value of wrinkle deformation is usually the only parameter considered during the mask mounting process. Indeed it is not enough to judge the qualification of FMM and to predict the evaporation defects. According to the authors' experiment and finite‐element method analysis, the size of the wrinkle and the slope angle of the wrinkle work together to affect the morphology of wrinkling under magnetic field and patterning defects. Further, the severe tilting angle of sheets is found to worsen the color‐mixing defects around the wrinkle.